PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PEMANFAATAN TEKNOLOGI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN PENGELOLAAN KEUANGAN SEBAGAI VARIABEL INTERVENING DI KABUPATEN PASURUAN - Primardiningtyas, Filzah; Hidayat, Muhammad Taufik (AKUNTANSI DEWANTARA, 2025)
With the use of intervening factors related to regional financial management in Pasuruan Regency, this research intends to examine the effects of accountability, transparency, and technology use on the quality of financial reports. This study makes use of quantitative methods, such as descriptive analysis and a census-based sampling strategy. A total of 87 respondents from each regional apparatus operation (OPD) were included in this research, all of them were members of the finance, budget, and treasury personnel. Information gathered from surveys and processed with the use of PLS 3 software, including both outside and inner model testing. The study found that several factors influence financial report quality: accountability, transparency, and technology use all have positive and significant effects on report quality; transparency has a positive but insignificant effect on report quality; financial management has a negative but insignificant effect on report quality; and regional financial management has no control over the variables of report quality that relate to technology use, transparency, and accountability.